2022
DOI: 10.22201/ib.20078706e.2022.93.3949
|View full text |Cite
|
Sign up to set email alerts
|

Plantas americanas utilizadas como condimento en la cocina mexicana

Abstract: La cocina de México forma parte de su identidad alimentaria, es reconocida por la gran diversidad biocultural y por la convergencia de raíces indígenas y extranjeras. El objetivo de esta contribución fue catalogar especies condimentarias de origen americano utilizadas en la cocina mexicana y proponer una clasificación de sus formas de uso y consumo. Se realizó una recopilación de datos a partir de bibliografía y consulta a la “Base de Datos Etnobotánicos de Plantas Útiles de México” del Jardín Botánico del Ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…5 ). The flavour of Piperaceae species is coriander-like and they have been used as condiments in many dishes since pre-Hispanic times ( Picó and Nuez 2000 ; Lascurain-Rangel et al 2022 ). Species are epiphytes common to cloud forests of the central area of the Province of the Gulf of Mexico ( Vergara-Rodríguez et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 ). The flavour of Piperaceae species is coriander-like and they have been used as condiments in many dishes since pre-Hispanic times ( Picó and Nuez 2000 ; Lascurain-Rangel et al 2022 ). Species are epiphytes common to cloud forests of the central area of the Province of the Gulf of Mexico ( Vergara-Rodríguez et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study identified several lineages scattered in the angiosperm tree used for food that are distinctive of certain ecosystems in the Province of the Gulf of Mexico, such as cloud forests characterized by abundant epiphytes ( Hietz and Hietz-Seifert 1995 ). Species in epiphytic genera, such as Peperomia , are utilized as condiment ( Lascurain-Rangel et al 2022 ), or like Oreopanax , a distant group in the phylogeny, which leaves are collected in the field for wrapping tamales ( Lascurain et al 2017 ). These results indicate that people are utilizing different lineages in the angiosperm tree available locally, for particular uses, like condiment or for wrapping food; moreover, phylogenetic metrics support these groupings depicted from the database.…”
Section: Discussionmentioning
confidence: 99%
“…En el estado de Yucatán se destinaron 312.65 ha para su cultivo, con un volumen de producción de 4 325.67 t con rendimientos promedios de 13.84 t ha −1 (SIAP 2022). Los frutos son de uso cotidiano en la cocina regional, se utilizan para elaborar salsas y productos nutracéuticos (Lascurain-Rangel et al 2022, Avilés-Bentazos et al 2023. Sin embargo, durante su cultivo la incidencia de enfermedades son una limitante, lo cual varía la producción en cada ciclo agrícola (Cristóbal-Alejo et al 2020).…”
Section: Introductionunclassified
“…H. A. Kenn & Nicolson, among others (Lascurain-Rangel et al 2017). Its use is due to the taste and aroma impregnated in the tamale's dough after cooking, which is highly appreciated by local consumers (Lascurain-Rangel et al 2022).…”
mentioning
confidence: 99%